Hubungan Membaca Pemahaman dengan Menulisa Karangan Argumentasi Siswa Kelas X SMA Negeri 1 Sungai Limau - Aminah, Ayu; Agustina, Agustina; Afnita, Afnita (Universitas Negeri Padang, 2012)
The purpose of this study describe (1) the ability of reading comprehension class X SMAN 1 Sungai Limau, (2) the ability to write essays arguing class X students of SMAN 1 Sungai Limau, (3) the relationship of reading comprehension skills with the ability to write an essay arguing SMAN 1 class X Sungai Limau. The data in this study were collected by using an objective test and a performance test. The findings of the study are (1) the ability of reading comprehension class X students of SMAN 1 Sungai Limau are in good qualification, (2) the ability to write essays arguing class X students of SMAN 1 Sungai Limau are more than enough to qualify, (3) there is a significant relationship between reading comprehension skills with the ability to write an argument essay class X SMAN 1 Sungai Limau.